ONTO-GNOSEOLOGICAL ASPECTS OF SCIENTIFIC INTELLIGENCE AND ITS IMPORTANCE - Kuchkarovich, Ramazanov Aziz (IJRDO Journal of Philosophy, culture and Religious study, 2022)
This article discusses the onto-epistemological aspects of scientific reasoning and its importance. The modern scientific landscape of the world is becoming increasingly systematic and integrated. Epistemologically, science emerges as one of the ways to know the world.